Five Rings : Orla Barry Rui Chafes. - Custodio, Ricardo; Barry, Orla; Museu Colecao Berardo, Lisboa (Lisboa : Fundacao de Arte Moderna e Contemporanea - Colecao Berardo, 2011., 2011)
Barry, Orla ; Chafes, Rui
Five Rings Orla Barry Rui Chafes, Museu Colecao Berardo, Lisboa, 02/05 21/08/2011
kunstcatalogus
Keywords: Barry, Orla; Chafes, Rui